HUBUNGAN KANDUNGAN MINYAK DENGAN KELIMPAHAN DIATOM DI PERAIRAN MERAL KARIMUN PROVINSI KEPULAUAN RIAU - Susammesin, Verid Aria; Nurrachmi, Irvina; Siregar, Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in February-March 2015 with a goal to determine the relationship between the oil content and the abundance of diatomsin Meral Karimun waters of Riau Islands Province. The survey method was applied in four stations with three sampling strata,i.e. the surface area, the middle and near the bottom. It revealed that the oil content of water ranged from 0.1797 to 0.2063 ppm and diatom abundance were between 44 to 149 cells/l, which contain of 14 species. Apparently, the oil content of seawater was not correlated (p>0.05) with diatom abundance were the coefficient correlation of (r) = 0.318. The regression equation was y = - 468.350x + 184.297 with a coefficient of determination (R2) =0.101 and a correlation coefficient (r) = 0.318. It was suggested that increasing oil content will decrease the abundance of diatoms in the Meral Karimun waters.Key Words:Meral,abundance, diatoms, oil content